The importance of applying the balanced scorecard to evaluate the strategic performance of private universities, a survey study of the opinions of a sample of stakeholders at Cihan University/Sulaimani. - Osman Abdelkader Hama Amin; Ghazi Abdul Aziz Suleiman Al-Bayati; Zhian Ehsan Kareem (The Scientific Journal of Cihan University– Sulaimaniya, 2017)
The aim of the study is to clarify the impact of the application of a balanced scorecard in the evaluation of the strategic performance of the university Cihan of sulaimanya. One of the civil universities in the sulaimanya governorate – survey study from the view of a sample of stakeholders in the university. That included a council of the university, number of personnel and students. Designed for the purpose of identifying the include five axes, representing the perspectives of a balanced scorecard, distribution images in the sample and subjected the data themselves. The results of the analysis were that the university did not apply a strategic balance scorecard when its assessment of performance and that the university administration was aware of the importance of the balance scorecard with their five perspectives. It also shows that the university administration deal fairly with students requested and don’t differ between them, for win their satisfactions about the services. the personnel in the whole need to develop their abilities. The study recommended the need to provide training opportunities for appropriate rehabilitation personnel, and the need for the introduction of modern teaching techniques when provides its services. It also recommended to the need to support the unity of the quality assurance and quality in the university and the provision of abilities that need.